The most demanding scenarios of 5-on-5 modified scrimmage situations in elite basketball - Vazquez-Guerrero, J.; Vizuete, J. J.; Garcia, F.; Hughes, J.; De Ste Croix, M. B.; Ayala, F. (The Journal of Sports Medicine and Physical Fitness, 2021)
BACKGROUND: The most demanding scenarios and physical demands of elite basketball 5-on-5 scrimmages are unknown to trainers, although recent advances in microtechnology allows the gaps in this research to be filled. The purpose of this study was to describe and compare the physical demands, through the most demanding scenarios and traditional average measures, of two different 5-on-5 scrimmage situations executed during training sessions in elite male basketball players. METHODS: Physical demand measures (i.e., total distance covered, high-speed running distance, number of high-intensity accelerations actions, number of high-intensity decelerations actions) were collected from 12 players from the Spanish first Division using a Local Positioning System. Measures were compared via a Bayesian inference analysis, considering playing in half-court (HALF) and half-court and transition (HTRAN) conditions for the 5-on-5 scrimmage. RESULTS: This study showed that, irrespective of the approach used to quantify the physical demands (traditional [average measures per minute] and novel rolling average time epoch [most demanding scenarios]), during the HALF condition players covered less and performed a lower number of high-intensity accelerations and decelerations than in HTRAN (Bayesian factor >10 and standardized effect size >0.6). Furthermore, players` physical demands during 5-on-5 scrimmage situations, independently of the court size, were underestimated consistently by the traditional approach. CONCLUSIONS: Quantifying players` physical demands through the rolling approach may provide a more accurate measure of the most intense periods of activity. Based on the physical demands described, HTRAN may be used to help train players to perform optimally during the most physically-stressful scenarios of match-play whereas HALF may be more suitable to be included in warm-ups, recovery sessions and sessions immediately before a match.